Método para seleção de um norma de certificação para segurança dos alimentos - Zanatta, Joice Aline Aguiar Cruz (2021)
Choosing a certification standard for food safety is a complex and conflicting decision as it involves numerous different criteria, such as cost, possibility of integration with other standards, scope, among others. This study aimed to propose a method to support decision making for choosing a certification standard related to food safety, as a tool to guide management decisions. Thus, initially, consultations were carried out on the official websites of each standard, to survey pre-selected criteria, and research was carried out with food safety experts, through a questionnaire, in order to validate the pre-defined criteria. Then, the multicriteria method to be applied (AHP) was selected, the method was applied in an industrial setting and the results were analyzed. The results obtained after applying the AHP method, applied in a large multinational food company, were the ranking of preference in relation to the certification standards, being, respectively, in order of preference, FSSC 22000, BRC, IFS and SQF. The results showed no inconsistencies in the results and were consistent with the number of certified standards in the current market. It is concluded that the AHP to support decision making for choosing certification standards for Food Safety proved to be effective. The work brings as a contribution the promotion of the use of methods to support decision-making, in different situations related to Food Safety, as recommended by the FAO. It is possible to conclude that decision support methods can be applied in similar themes. As Brazil is one of the largest food producers in the world, it can count on relevant contributions from the application of decision support methods. Future work can be carried out applying the proposed method in other scenarios, such as small and medium-sized and national companies.